2016
DOI: 10.1080/13603116.2016.1184328
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of university life for students with Asperger’s Syndrome: a comparative study between Spain and England

Abstract: Research has consistently shown that young people with Asperger's Syndrome (AS) are likely to experience increased anxiety during new social situations yet studies have been regionally and culturally bound with no sense of how experiences or practice differs across countries. The aim of this study was to explore how higher education students with AS experienced attending university in two European countries: the UK and Spain. The objective was to find out if experiences differed between the two countries in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…I resorted to a tutor who helped me'. (Casement et al, 2017) 'Students with sensory impairments should have the opportunity to attend a similar event without 'the noise and the crowds', or have a choice of having mentoring support or a personal assistant in attending such events'. (Madriaga, 2010) physical sensation (Goldfarb et al, 2021).…”
Section: My Sensory Processing and Othersmentioning
confidence: 99%
“…I resorted to a tutor who helped me'. (Casement et al, 2017) 'Students with sensory impairments should have the opportunity to attend a similar event without 'the noise and the crowds', or have a choice of having mentoring support or a personal assistant in attending such events'. (Madriaga, 2010) physical sensation (Goldfarb et al, 2021).…”
Section: My Sensory Processing and Othersmentioning
confidence: 99%
“…(Quinn et al, 2014;Retherford and Schreiber, 2015;Siew et al, 2017) • The following kinds of accommodations tended to be reported as helpful: extra time for tests, copy of notes or a note taker, technology supports, alternate testing sites, extensions, etc. (Barnhill, 2016;Anderson and Butt, 2017;Casement et al, 2017;Davidson et al, 2021) • Others noted lack of academic supports or of the availability/efficacy of existing supports (Zeedyk et al, 2019;Vadnjal and Radoja, 2020) • Some experienced lack of flexibility and understanding from professors and failure to implement accommodations (Accardo et al, 2019a;Bailey et al, 2020) or an unsupportive environment (Gurbuz et al, 2019;Fabri et al, 2020;Anderson et al, 2020b) • Need for flexibility in classroom and in structure of degree programs (Cai and Richdale, 2016;Sarrett, 2018; Howes, 2020)…”
Section: Socialmentioning
confidence: 99%
“…• Lack of (or inadequate) supports for transition into university, identified as a source of stress, anxiety, fear (Anderson and Butt, 2017;Shmulsky et al, 2017;McMorris et al, 2019;Ames et al, 2022) • "Culture shock" with lack of structure and overwhelming sensory environment (Van Hees et al, 2015;Vincent et al, 2017;Cage and Howes, 2020) • Need for assistance navigating to and on campus (Casement et al, 2017) • Some orientation activities were too overwhelming (Goddard and Cook, 2022) Transition out of PS:…”
Section: Categories Contributors Challengesmentioning
confidence: 99%
“…While social classes, gender and age are clear foci in the literature about inclusion in higher education, SEN is a more silenced area here, as compared to the literature on pre-tertiary education. Those limited studies focus mainly on the challenges of including students with autism spectrum disorder (Casement et al, 2017), physical disabilities (Evans, 2017) and specific learning difficulties such as dyslexia (Cameron and Billington, 2017). Clearly, access is not the only determinant of inclusion in these studies, as overcoming the challenges of marginalisation during student education is also important.…”
Section: Neoliberalism and Inclusion: Conflicting Or Mutually Constitmentioning
confidence: 99%